An empirical analysis of corporate ownership influence on voluntary greenhouse gas disclosure - Chen, Wenxi (2022)
As climate change and global warming have become hot topics in recent decades, the outcome of carbon disclosure conveying information related to corporate carbon performance, decarbonization target, environmental risks and opportunities is viewed as a strategic decision-making issue for enterprises in the growing competitive market. While exploring firm-specific drivers of voluntary carbon disclosure is a subject of lively debate, it remains underdeveloped and inconclusive in the relevant academic literature (Alsaifi et al., 2020). This study is motivated by the research gap and growing concerns about organizational proactivity on carbon initiatives, in order to examine the link between ownership structures and greenhouse gas disclosure. In line with legitimacy theory, agency theory, and signaling theory as the theoretical framework, it is expected to investigate whether different types of shareholders play stimulating roles in voluntary carbon reports, as evidenced by firms’ participation in the Carbon Disclosure Project. Using both univariate and regression models with a sample of the S&P 500 companies from 2015 to 2020, the empirical results indicate diverse ownership structures have distinct impacts and preferences in corporate carbon disclosure. The involvement of state ownership could promote transparency of carbon information while institutional shareholders, insider ownership, and blockholders appear negatively related to proactive greenhouse gas disclosure. These findings provide practical insights for management, regulators, and policymakers to focus on the configuration of corporate ownership in the context of improving green practices.